Contesting human knowledge and god - Chen, A (2018)
This dissertation is as much a study of Enlightenment intellectual history as a reflection on the Enlightenment as a historiographical concept. It reconstructs George Berkeley's writings so as to explore his dialectics of Enlightenment in terms of the conceptual conflicts between two languages of Enlightenment. It challenges (1) the predominant philosophical explication of Berkeley's thought that places him in philosophical traditions such as idealism and empiricism, (2) recent histories of Berkeley's 'non-philosophical' writings that tend to interpret him in the light of historiographical arguments about Enlightenment political economy and, in turn, take him as a case for the Irish participation in European Enlightenment, and (3) the historiographical conception of the Enlightenment that is preoccupied with the secular modernity thesis. The Introduction analyses the two historiographical grounds of this dissertation – Berkeley studies and Enlightenment intellectual history, and explains how this thesis intends to interact with these discourses. Chapter I explicates how Berkeley exposed the methodological failure of the new science, and shows why Berkeley thought a mathematically informed natural philosophy would threaten the stability of a protestant state. Chapter II delineates Berkeley's argument for the reasonableness of Christianity by tracing his demonstration of the divine being through a cooperation between metaphysics and natural philosophy. Chapter III shows Berkeley's criticism of the new science's theories of progress that defined 'an Enlightened age' as an improved human condition after the emancipation of rational agency from ecclesiastical and political authorities. Chapter IV turns to Berkeley's own theory of improvement based on his understandings of the socio-economic difficulties in eighteenth-century Ireland. Chapter V examines Berkeley's concern about the actual, social consequences of free-thinkers' theories of progress. Chapter VI explores Berkeley's argument for a genuine, theological Enlightenment as a counterpart to the religiously heterodox Enlightenment. The Conclusion asks the question about the relevance of this thesis, drawing attention to the idea of a critical and self-critical historiography as a way to re-accessing secular modernity's sense of historicity.